Perceptions and Knowledge of Public Towards Emerging Human Monkeypox in Yemen: A Cross-Sectional Study - Halboup, Abdulsalam M.; Alzoubi, Karem H.; Abu-Farha, Rana K.; Harun, Sabariah Noor; Al-Mohamadi, Ahmed; Battah, Mohammed M.; Jaber, Ammar Ali Saleh; Alkubati, Sameer; Al-Ashwal, Fahmi Y. (Dove Medical Press, 2023)
Background: The spread of monkeypox (mpox) worldwide poses a severe threat to human life. This virus leads to a disease with symptoms similar to smallpox in humans. To combat this threat, improving public knowledge and perception toward mpox is vital for public health preventive measures. Methods: A cross-sectional survey was carried out in Yemen from December 2022 to March 2023 to investigate public perception and knowledge of mpox. Individuals were approached through social media platforms using a convenient sampling approach. Linear regression was used to determine the association between participants knowledge (dependent variable) and explanatory variables. Results: A total of 853 individuals consented to take part in the study. A significant proportion of respondents had a low knowledge level (N=572, 67.06%). Most participants knew about the nature of the diseases (75%, n=641), transmission mode (78.1%, n=668), hand sanitizer preventive measures, and skin- related symptoms. However, only 20.8% (n= 178) knew that diarrhea is not a symptom, and 25.4% (n= 217) knew antibiotics are unnecessary for mpox management. A proportion of 57.7% (n=492) of the participants feared human mpox, and 47.7% (n= 407) thought it was a conspiracy. Most participants had a good perception of local and international health authorities controlling the disease. Age, education level, having a health-related certificate, and receiving a 2-dose vaccination for COVID-19 had statistically significant associations with mpox knowledge level (P < 0.05). Social media platforms were the most often used information source about mpox (78.3%, n= 668), followed by articles (41.1%, n=351). Conclusion: The study reveals a low public knowledge about mpox in Yemen, emphasizing the need for targeted educational campaigns, especially via social media, to strengthen public health measures and disease control. Addressing Knowledge gaps and correcting misconceptions is crucial for improving preparedness and response to the disease.